'Our dream is simple: Peace, safe and freedom': Regime-critical activism and artistic expression by Syrians in Denmark and Sweden. (1st April 2020) - Wessels, Josepha Ivanka (Joshka)
This article seeks to understand mediatized dynamics of regime-critical activism and cultural performances by Syrians in Europe. The focus of this research is on the Öresund-region between Denmark and Sweden. Sweden was the first country in Europe to give immediate permanent residence to Syrian refugees. It initially received most of the Syrian refugees in 2015. After the arrival of large groups of Syrians at Malmö station in that year, a growing network of volunteers responded to the influx of refugees. Syrians started to build relationships with local activists and have since joined in organizing publicly mediated events, creating a new landscape for creative industries and performance arts in the region. Applying a protest communication ecology approach, I use a wide definition of media which includes the aesthetics of street demonstrations, performance arts and music, mediated and communicated through digital online platforms. I apply an adjusted concept of communitas, including digital media and online communication as analytical concept to observe and describe not only how communitas is re-formed between Syrian refugees after arrival but also how it emerges between Syrians and local hosts.